STUDY OF THE EFFECT OF FIBER TYPE AND THE NUMBER OF REINFORCING LAYERS ON SOME MECHANICAL PROPERTIES OF POLYMERIC OVERLAYS - FAYIC H. ANTER; MISHAAN K. SALIH (مجلة جامعة الانبار للعلوم الصرفة, 2017)
This work includes preparation polymeric composite materials by hand-lay up method layers of glass fiber type ( E-glass) and Rock wool fiber at volume fraction 30%. Practical results showed that the surface hardness and impact strength increase with increasing the number of reinforcing layers for the two types of fibers . Also the results showed that the values of hardness and impact strength for the samples reinforced with glass fiber more than that of samples reinforced with rock wool fibers.